2010
DOI: 10.1111/j.1464-410x.2010.09333.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bladder neck contracture after robot‐assisted laparoscopic and open radical prostatectomy

Abstract: OBJECTIVE To evaluate the incidence and risk factors for bladder neck contracture (BNC) in men treated with robot-assisted laparoscopic radical prostatectomy (RALP) and open radical prostatectomy (ORP), as BNC is a well-described complication of ORP and may be partially attributable to technique. PATIENTS AND METHODS The University of California San Francisco Urologic Oncology Database was queried for patients undergoing RALP or ORP from 2002 to 2008. Patient demographics, prostate cancer-specific informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 22 publications
1
64
0
4
Order By: Relevance
“…In the contemporary literature, bladder neck contractures are reported in 0 to 7.4% of RALP patients and in 2.6 to 9% of patients after open radical prostatectomy (9,10,12,17,18). The exact cause of bladder neck contracture is not known although several theories exist.…”
Section: Discussionmentioning
confidence: 99%
“…In the contemporary literature, bladder neck contractures are reported in 0 to 7.4% of RALP patients and in 2.6 to 9% of patients after open radical prostatectomy (9,10,12,17,18). The exact cause of bladder neck contracture is not known although several theories exist.…”
Section: Discussionmentioning
confidence: 99%
“…Совре-менные достижения в лечении РПЖ позволили мини-мизировать число послеоперационных осложнений, в том числе стриктуры ВУА, тем не менее частота ее развития по-прежнему остается высокой и варьирует от 0,7 до 10,0 % [15]. По мнению разных авторов, в группе больных, перенесших РАРПЭ, частота выяв-ления стриктуры ВУА достигает 28,7 %, в то время как после открытой РПЭ этот показатель несколько выше -29,3 % [16][17][18]. Подчеркнем, что на вероят-ность развития стриктур ВУА могут влиять такие фак-торы, как неадекватное сопоставление тканей слизистой оболочки шейки мочевого пузыря и моче-испускательного канала, недостаточная герметичность анастомоза, длительная ишемия и деваскуляризация шейки мочевого пузыря, анатомическая узость уре-тры, проведение гормональной терапии перед опера-цией, перенесенные ранее трансуретральная резекция предстательной железы и дистанционная лучевая те-рапия, а также опыт хирурга [19][20][21][22].…”
Section: Discussionunclassified
“…Bladder neck contracture (BNC) is a known complication of RP. Breyer et al [36] reported that the BNC rate was 1.4 % for RALP and 2.6 % for ORP. Webb et al [37] also reported that RALP was superior to ORP in the incidence of BNC.…”
Section: Fig 2 Pooled Estimates Of Operation Durationmentioning
confidence: 99%